2023
DOI: 10.1142/s0217751x23500288
|View full text |Cite
|
Sign up to set email alerts
|

Features of gravitational interaction as the basis of “Dark Energy” in the gas of null strings

Abstract: In this work, the influence of the shape of the null strings that form the gas on the gravitational properties and evolution of the null string gas was investigated. An interesting result of the study is that the test null string, being in the interaction zone, can only have a shape that exactly repeats the shape of the source string. As a result, null strings having different spatial forms can be located in the gas only outside the zone of interaction with each other. The “size” (width) of the zone of interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…As already mentioned in section 3, in work [70] the influence of the gravitational field of a thin tube of a massless scalar field (source string), the quadratic form of which is determined by equalities (1)-( 4), on the motion of a test null string was studied. The study showed that each tube of the scalar field has its own zone of interaction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As already mentioned in section 3, in work [70] the influence of the gravitational field of a thin tube of a massless scalar field (source string), the quadratic form of which is determined by equalities (1)-( 4), on the motion of a test null string was studied. The study showed that each tube of the scalar field has its own zone of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for some values of these constants, the 'width' (size) of the interaction zone of one thin tube of a scalar field can occupy the entire space. An important result obtained by [70] is that only strings (thin tubes) that have the same spatial shapes can be found inside the interaction zone. In other words, thin tubes of a scalar field, which have different spatial shapes, can only be located in a gas outside the zone of interaction with each other.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations